Acute urinary retention due to corpus cavernosum penile metastasis from lung adenocarcinoma after targeted therapy: a case report and review of the literature - Yan, Wei; Fu, Hui; Liu, Huiqun; Liu, Zhentian; Qi, Xueliang; Chen, Tanxiu (Frontiers in Oncology, 2024)
Background: Metastasis in penile corpus cavernosum from adenocarcinoma of lung is a rare but fatal disease, which was reported in cases without series studies. It causes various clinical symptoms seriously affecting the quality of life.Case presentation: A 72-year-old male smoker patient, who had a history of adenocarcinoma of lung after targeted therapy 36 months before, was admitted to Jiangxi Cancer Hospital because of presenting with aggressive dysuria and penis pain for one hour. A Foley catheter was inserted into the patient's bladder with difficulty. Immediately do a bladder puncture. Emergency pelvic computed tomography (CT): a soft tissue nodule of 1.1 cm×1.4 cm was found in the cavernous area of the middle part of the penis, and the proximal urethra was dilated with a wide diameter of about 1.5 cm. The diagnosis of metastatic lung adenocarcinoma from the primary was made by CT-guided biopsy.The penis may be a site of metastasis from primary lung cancer, especially for old patient. Metastasis to the penis usually indicates that the primary lung cancer is at an advanced stage and the prognosis is very poor. More research is necessary to understand the underlying mechanism of adenocarcinoma of lung metastasis.